Acute generalized exanthematous pustulosis induced by ceftriaxone use - Nacaroglu, Hikmet Tekin (Termedia Publishing House, 2014)
Acute generalized exanthematous pustulosis (AGEP) is a rare cutaneous rash characterized by the abrupt onset of a generalized pustular rash often accompanied by fever. There is a history of drug use in 90% of the cases. Here we have reported a 15-year-old male patient with sickle cell anemia who developed AGEP after the use of ceftriaxone. Our patient was hospitalized because of vaso-occlusive crisis and on the third day of ceftriaxone treatment, erythematous pustular lesions accompanied with fever were observed on the body and extremities. Resolution of symptoms followed discontinuation of ceftriaxone. Sensitivity to ceftriaxone was shown with a patch test. The AGEP was considered due to clinical and histopathological findings. This is the first pediatric case of AGEP due to ceftriaxone.